(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the agricultural development strategy of the Arnasay region, especially in the context of problems associated with water shortages and land degradation. The authors analyze the current state of agriculture and highlight the need for optimal use of land resources and innovation to improve sustainability and food security. Particular attention is paid to the prospects of organic farming and methods that help improve the quality of the land. The article proposes an integrated approach to solving environmental and economic problems facing regional agriculture.